A rare case of bladder gangrene associated with inguinal hernia: case report - Gayathre, S. P.; Kudiyarasu, M.; Baskaran, Aarthy (International Surgery Journal, 2023)
Involvement of bladder in inguinal hernia is rare and occurs in less than 5% of the cases and strangulated inguinal hernia has an overall prevalence of 1.3% affecting mainly senile patients. Bladder gangrene associated with strangulated inguinal hernia is an extremely rare entity and only one case has been reported so far. We report a rare case of strangulated left inguinal hernia with bladder and bowel as content and with gangrene of both. A 42-year male presented with left inguinal irreducible swelling with features of obstruction for 2 days with no urological symptoms. Preoperative CT abdomen revealed obstructed left direct inguinal hernia with jejunum and omentum as content. Emergency laparotomy done and it revealed an indirect sac containing bladder with supratrigonal bladder gangrene and gangrenous ileum. Partial cystectomy and resection and anastomosis of ileum with herniorrhaphy was done.